2002
DOI: 10.1080/10428190290021579
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 in Myeloma Cells

Abstract: In addition to interleukin (IL)-6, IL-10 is considered as one of the most important cytokines regulating the proliferation and cellular characteristics of myeloma cells. It is still unclear from the clinical data how serum IL-10 levels of various stages of myeloma, are related to clinical manifestations of this disease. Several studies have reported that IL-10 affects myeloma cells by stimulating secondary signals for cell proliferation through oncostatin M (OSM) and IL-11. In experiments using human myeloma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…11,14,15 The anti-inflammatory cytokine IL-10 has also been shown to provide direct growth support to myeloma cells. 16,17 Whereas IL-1b and TNF-a mainly act by activating the nuclear factor kB (NF-kB) pathway in myeloma cells, 18,19 IL-6 and IL-10 exert their complex actions through the Janus kinase/signal transducer and activator of transcription pathway as well as the mitogen-activated protein (MAP) kinase and phosphatidylinositol 3-kinase/AKT pathways. 20,21 Durie and coauthors highlighted the importance of macrophages as a potential source of paracrine inflammatory cytokines in myeloma in an early study.…”
Section: Introductionmentioning
confidence: 99%
“…11,14,15 The anti-inflammatory cytokine IL-10 has also been shown to provide direct growth support to myeloma cells. 16,17 Whereas IL-1b and TNF-a mainly act by activating the nuclear factor kB (NF-kB) pathway in myeloma cells, 18,19 IL-6 and IL-10 exert their complex actions through the Janus kinase/signal transducer and activator of transcription pathway as well as the mitogen-activated protein (MAP) kinase and phosphatidylinositol 3-kinase/AKT pathways. 20,21 Durie and coauthors highlighted the importance of macrophages as a potential source of paracrine inflammatory cytokines in myeloma in an early study.…”
Section: Introductionmentioning
confidence: 99%
“…four of ten human myeloma cell lines produce IL-10 spontaneously [6,7] . Elevated IL-10 levels were detected in serum from about 50% of patients having multiple myeloma showing a relation to the clinical manifestation [8] . IL-10 exerts its biologic effects on cells by specific cell surface receptors which are composed of two distinct subunits, activating the JAK/STAT signalling pathway.…”
Section: Measurement Of the Proliferationmentioning
confidence: 99%
“…24 We used RT-PCR to examine whether nucleosomes increased IL-8 mRNA, as well as other angiogenic cytokines and growth factor mRNAs known to be expressed in endothelial cells or tumor tissue, namely, IL-6, IL-10, TNF-␣, VEGF and FGF-2. [25][26][27][28][29][30] Comparison of the angiogenesis-related mRNAs with 2 housekeeping genes indicated that nucleosomes increased IL-6 and IL-8 mRNA 3-and 5-fold, respectively (Fig. 3).…”
Section: Nucleosomes Induce Il-8 Mrna In Huvecsmentioning
confidence: 99%